Weakening Otherworldliness: Vattimo, Hermeneutics, and the Question of Contemptus Mundi - Ambord, Daniel (Diakrisis, 2024)
The lineage of philosophical hermeneutics is indelibly marked by the discourse of asceticism and otherworldliness. This influence springs most immediately from Nietzsche but finds itself provocatively manifest in the recent and ongoing return of philosophical hermeneutics to religious patterns of thought. This work will consider the hermeneutic encounter with and appropriation of asceticism in the work of Gianni Vattimo. In one sense, this engagement would appear an unlikely one, as Vattimo (following Nietzsche) is openly suspicious of the voluntary assumption of and salvific role for suffering in the quest for human flourishing. However, upon closer inspection, we see that a reconfigured asceticism, focused on the turning of power against itself and the reconfiguration of our relationship with the world, is alive and well in Vattimo’s "weak thought." More radically, Vattimo’s thought represents a purification-even a mortification- of asceticism by cleansing it of its untenable and burdensome metaphysical baggage and allowing for a renewed and authentic approach to religiosity.